Fundamentals of Space Business and Economics - Gurtuna, Ozgur; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book provides an overview of key topics related to space business and management. Case studies and an integrative section are included to illustrate the fundamental concepts and to build intuition. Key topics in the field, such as risk management and cost management, are covered in detail.
Introduction to Space Business and Economics -- Understanding the Nature of Space Business -- Socio-economic Benefits of Space Activities -- Emerging Space Markets -- Key Issues and Challenges in Space Business -- Risk Management -- Cost Management -- Putting It All Together - Assessing the Feasibility of a New Project/Venture.
Keywords: Economics; Astrophysics; Astronautics; System safety; Economics/Management Science; Innovation/Technology Management; Extraterrestrial Physics, Space Sciences; Aerospace Technology and Astronautics; Quality Control, Reliability, Safety and Risk